Axl is a key regulator of intestinal γδ T‐cell homeostasis. Issue 12 (25th September 2019) - Kim, Su‐Man; Park, Min; Yee, Su‐Min; Ji, Kon‐Young; Lee, Eun‐Hee; Nguyen, Thi‐Van; Nguyen, Thi Hong‐Loan; Jang, Jin; Kim, Eun‐Mi; Choi, Ha‐Rim; Yun, Chul‐Ho; Kang, Hyung‐Sik
Abstract : Gut‐homing γδ T cells are induced by chemokines and cell adhesion molecules and play a critical role in homeostasis and mucosal immunity; however, little is known regarding their upstream regulators. We investigated the role of Axl as a specific regulator of chemokines and cell adhesion molecule in the distribution of intestinal γδ T cells. The population of γδ T‐cell receptor‐positive cells including Vγ1 and Vγ7 subsets was remarkably increased in the intraepithelial lymphocytes of Axl mice compared with those of wild‐type (WT) mice. An increased number of migrated γδ T cells were observed in the coculture with intraepithelial cells from Axl –/– mice. The mRNA expression level of chemokine (C‐C motif) ligand (CCL) 25 was specifically higher in the small intestine of Axl –/– mice than in WT mice. In adoptive transfer, the migration of both thymic and extrathymic γδ T cells was increased in Axl –/– mice. The activation of Axl signaling down‐regulated CCL25 expression via ERK signaling pathway and reduced the population of γδ T cells. Systemic dissemination was suppressed in Axl –/– mice infected with Salmonella typhimurium. Thus, our findings suggest that Axl plays a critical role in regulating the migration of γδ T cells for the maintenance of homeostasis and bacterial resistance.—Kim, S.‐M., Park, M., Yee, S.‐M., Ji, K.‐Y., Lee, E.‐H., Nguyen, T.‐V., Nguyen, T. H.‐L., Jang, J., Kim, E.‐M., Choi, H.‐R., Yun, C.‐H., Kang, H.‐S. Axl is a key regulator of intestinal γδ T‐cell homeostasis. FASEB J. 33, 13386–13397 (2019). www.fasebj.org